A hexagon in Saturn’s northern stratosphere surrounding the emerging summertime polar vortex - L. N. Fletcher; G. S. Orton; J. A. Sinclair; S. Guerlet; P. L. Read; A. Antuñano; R. K. Achterberg; F. M. Flasar; P. G. J. Irwin; G. L. Bjoraker; J. Hurley; B. E. Hesman; et al. (Nature Communications, 2018)
The Cassini spacecraft has provided an unprecedented characterisation of seasonal changes on Saturn. Here the authors describe the development of a warm polar vortex in Saturn’s northern summer, and show that the hexagon extends hundreds of kilometres from the troposphere into the stratosphere.